Health significance of body position during sleep - literature review - Sudelska, Katarzyna; Sawińska, Zuzanna; Tarsa, Grzegorz; Kępka, Przemysław; Łokczewska-Bojar, Aleksandra; Kuziemkowska, Daria; Kuźma, Jan; Ben Rhaiem, Rami; Skotalczyk, Magdalena; Łącka-Majcher, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Sleep is a fundamental biological need of the body, crucial for maintaining health and body’s regeneration. The body position during sleep not only affects sleep quality and well-being but also influences various health aspects, such as obstructive sleep apnea, back pain or gastroesophageal reflux. Aim of the study: The aim of our study is to summarize the impact of body position during sleep on human health. We paid attention to the relationship between sleep position and aspects like: sleep quality, obstructive sleep apnea, back pain and gastroesophageal reflux. State of knowledge: The body position during sleep is crucial for maintaining mental and physical health. It affects sleep quality as well as health aspects such as: obstructive sleep apnea, back pain or gastroesophageal reflux disease. In the case of sleep quality, the most beneficial position is on the right side. The supine position is associated with worsened obstructive sleep apnea, while on the side - with reducing the frequency of symptoms. Neck pain is connected with an asymmetrical side and an upright head position, while lower back pain is associated with a supine position. The described position that reduces the reflux of gastric contents into the esophagus, and thus reduces the symptoms of reflux disease, is on the left side and with an elevated head of the bed. Summary: Sleep position is significant for many aspects of human health. Besides affecting sleep quality and well-being, it also has an impact on conditions such as obstructive sleep apnea, back pain and gastroesophageal reflux.